Assessment of the Pelvic Floor and Associated Musculoskeletal System: Guide for Medical Practitioners. Issue 12 (December 2021) - Harm-Ernandes, Ingrid; Boyle, Valerie; Hartmann, Dee; Fitzgerald, Colleen M.; Lowder, Jerry L.; Kotarinos, Rhonda; Whitcomb, Emily
Abstract : Objectives: This study aimed to assist practitioners in performing an accurate assessment of the external and internal pelvic musculoskeletal (MSK) systems to improve appropriate diagnosis and referral of patients with pelvic floor disorders or pelvic pain and to improve understanding of physical therapy (PT) treatment principles, thereby improving communication between practitioners and encouraging a multidisciplinary approach. Methods: A referenced review of the anatomy of the pelvic floor muscles, pelvis, and surrounding structures, followed by a detailed assessment of anatomy, posture, and gait, is presented. A thorough description of PT assessment and treatment is included with clinical relevance. Results: When proper assessments are routinely performed, MSK conditions can be recognized, allowing for prompt and appropriate referrals to PT. Assessment and treatment by qualified physical therapists are integral to pelvic health care. After efficient medical assessment, MSK dysfunction can be addressed expeditiously, thereby avoiding further decline. Left unaddressed, pelvic dysfunction may become chronic. Conclusions: We propose a guide for MSK assessment of the pelvis and associated structures that can be used for both clinical and research purposes. This guide is designed for health care providers caring for women with pelvic floor disorders, including physicians, advanced practice providers, and nurses. This guide serves to improve communication among multidisciplinary practitioners to refine MSK assessment and treatment approaches and thereby advance clinical care and research. Abstract : Supplemental digital content is available in the text.